PERSEPSI PRAKTISI DAN PENGGUNA JASA AKUNTAN FORENSIK TERHADAP KEAHLIAN AKUNTAN FORENSIK - Retno Tri Handayani (Jurnal Akuntansi Indonesia, 2018)
This study aims to determine the perceptions of practitioners and users of forensic accountants about the expertise of forensic accountants. The population of this research are BPK and BPKP as practitioners of forensic accountant and prosecutor and judge as user of forensic accountant service in Semarang and Yogyakarta city. Population in this research amounted to 403. Sampling was done by technique of Purposive Sampling and obtained sample counted 253 respondents. This study used ANOVA test and if the result is significant continued with Tukey test. The results show that there is no difference in the perceptions of practitioners and users of forensic accounting services about the skills of a forensic accountant. Likewise, this study proves that practitioners and users of forensic accounting services are no different. The study alsofound that practitioners and users of forensic accountants agree differently on the importance of deductive analysis skills, critical thinking skills, unstructured problem solving, analytical skills, oral communication, legal knowledge and tranquility. The implications of this study are expected in the preparation of forensic accountant curricula can refer to the results of this study